2015
DOI: 10.1007/s10482-015-0546-8
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol production by yeasts isolated from rotting wood in the Galápagos Islands, Ecuador, and description of Cyberlindnera galapagoensis f.a., sp. nov.

Abstract: This study evaluated D-xylose-assimilating yeasts that are associated with rotting wood from the Galápagos Archipelago, Ecuador, for xylitol production from hemicellulose hydrolysates. A total of 140 yeast strains were isolated. Yeasts related to the clades Yamadazyma, Kazachstania, Kurtzmaniella, Lodderomyces, Metschnikowia and Saturnispora were predominant. In culture assays using sugarcane bagasse hemicellulose hydrolysate, Candida tropicalis CLQCA-24SC-125 showed the highest xylitol production, yield and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…nov. CLQCA-24SC-025, from the Galápagos Archipelago, Ecuador Guaman-Burneo, Dussan. 50 The authors reported similar results (Y P/S = 0.64 g g −1 , Q P = 0.33 g L −1 h −1 , η = 70.58%) in the fermentation of hemicellulosic hydrolysate from sugarcane bagasse to those obtained in the present work.…”
Section: Scheffersomyces Amazonensissupporting
confidence: 87%
“…nov. CLQCA-24SC-025, from the Galápagos Archipelago, Ecuador Guaman-Burneo, Dussan. 50 The authors reported similar results (Y P/S = 0.64 g g −1 , Q P = 0.33 g L −1 h −1 , η = 70.58%) in the fermentation of hemicellulosic hydrolysate from sugarcane bagasse to those obtained in the present work.…”
Section: Scheffersomyces Amazonensissupporting
confidence: 87%
“…In addition to acetic acid, the hydrolysate may contain other inhibitors such as furfural and HMF, which combined can affect yeast growth and fermentation (Almeida et al 2008;Deparis et al 2017). Since hydrolysate tolerance is species and strain-dependent (Modig et al 2008), and since many studies have already shown that C. tropicalis can produce xylitol with high yields and productivities on fermentative medium containing hydrolysates (Cadete et al 2012;Guamán-Burneo et al 2015;Mattam et al 2016;Dalli et al 2017), a C. tropicalis strain isolated by our group (C. tropicalis CMAA1716 strain, unpublished data) was used as a control in this experiment.…”
Section: Fermentation Of Sugarcane Biomass Hydrolysatementioning
confidence: 99%
“…Among those, yeasts have been reported to be the most efficient xylitol producers (Albuquerque et al 2014;Pal, Mondal and Sahoo 2016). Previous studies involving approximately 40 species, belong to 18 different yeast genera, have identified Candida guilliermondii (currently Meyerozyma guilliermondii (Kurtzman and Suzuki 2010)) and Candida tropicalis as prominent xylitol producers, with production yields up to 0.59 g/g and 0.67 g/g, respectively (Barbosa et al 1988;Guamán-Burneo et al 2015). Recently, new species described as Cyberlindnera galapagoensis, Scheffersomyces amazonensis and Spathaspora spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…forestry residues, are used (Mello Lourenco et al 2014; Kamat et al 2013; Guamán-Burneo et al 2015). It was reported that the yeasts adapted to these environments were expected to have high ability to convert xylose to xylitol.…”
Section: Resultsmentioning
confidence: 99%